2022
DOI: 10.1186/s42269-022-00734-y
|View full text |Cite
|
Sign up to set email alerts
|

Litsea cubeba fruit attenuates diabetes-associated metabolic complications in mice

Abstract: Background Litsea cubeba (Lour) Pers. (Lauraceae) fruit has traditionally been used in treatment of diabetes in Sikkim, India. The purpose of the present study is to investigate the antidiabetic activity of methanol extract of Litsea cubeba fruit (MELCF) against streptozotocin (STZ)-induced diabetes in male albino mice. MELCF was assessed for in vitro α amylase, α glucosidase inhibitory activity and in vitro antioxidant activity against 2-diphenyl-1-picrylhydrazyl (DPPH) and nitric oxide radica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 22 publications
0
1
0
Order By: Relevance
“…The main pharmacological effects of the plant include relief from epigastric discomfort, reduced vomiting and hiccups, and enhanced immune function ( 19 ). For example, Goldar et al ( 22 ) found that the fruit of L. cubeba significantly alleviated diabetic complications in mice. However, to the best of our knowledge, L. cubeba has not been tested as an additive to improve broiler health and meat quality.…”
Section: Introductionmentioning
confidence: 99%
“…The main pharmacological effects of the plant include relief from epigastric discomfort, reduced vomiting and hiccups, and enhanced immune function ( 19 ). For example, Goldar et al ( 22 ) found that the fruit of L. cubeba significantly alleviated diabetic complications in mice. However, to the best of our knowledge, L. cubeba has not been tested as an additive to improve broiler health and meat quality.…”
Section: Introductionmentioning
confidence: 99%